Impacts of prenatal and environmental factors on child growth: Evidence from Indonesia - Yamauchi, Futoshi; Higuchi, Katsuhiko; Suhaeti, Rita Nur (International Food Policy Research Institute, 2009)
This paper examines the impacts of prenatal conditions and water quality on child growth using recent data from Indonesia. Our empirical results show that an increase in birth weight has significant positive effects on children’s subsequent height- and weight-for-age Z-scores, whereas an improvement in drinking water quality, as measured by coliform bacteria count, increases the weight-for-height Z-score. Interestingly, there is seasonality in birth weight; this measure is significantly higher during the dry season than during the rainy season, and is also higher also in a Christian-majority province than in Muslim-majority provinces, during the period shortly after Ramadan. Finally, the availability of modern water infrastructure improves the quality of drinking water. These findings show that interactions of ecological and technological variations affect early childhood human capital formation and can have long-term impacts on their outcomes. Two policy implications follow. First, public investments in infrastructures capable of improving drinking water quality (for example, piped water facilities) and smoothing seasonal fluctuations of food production/supply (for example, advanced markets and distribution networks) could be expected to promote early childhood human capital formation. Second, we highly recommend educational campaigns that emphasize the importance of clean drinking water to families, and advise mothers (especially those whose expected due dates are in the January-April period) to take birth-weight-increasing measures, such as the consumption of additional nutrition.